Π‐Plasmon absorbance films of carboxylic functionalized CNTs coupled with renewable PGP platforms. (10th April 2018) - Fares, Mohammad M.
Abstract : π‐Plasmon absorbance films of carboxylic functionalized multiwall carbon nanotubes (CNTs) coupled with renewable and recycled polycaprolactone grafted pectin (PGP) platforms as successful alternative for ordinary nondegradable platforms were investigated. Characterization of the synthesized carboxylic functionalized CNTs was performed using 1 H NMR and attenuated total reflectance Fourier transform infrared for structural identification, thermogravimetric analysis and derivative thermogravimetric analysis for thermal stability, and X‐ray powder diffraction for crystal structure, whereas the characterization of prepared PGP was done by means of attenuated total reflectance Fourier transform infrared for chemical structure, differential scanning calorimetry for melting endotherms of polycaprolactone and high crystalline structure of PGP, and thermogravimetric analysis and derivative thermogravimetric analysis for thermal stability of PGP. Fabrication of water‐dispersed carboxylic functionalized CNTs coupled with PGP films was performed by casting technique in the presence of Ca 2+ as cross‐linker. The thin films were tested for π‐plasmon absorbance using UV‐Vis spectrometry. Different fractions of carboxylic functionalized CNTs and PGP films demonstrated π‐plasmon absorbance broad peaks at λmax  = 232 nm, which corresponded to 5.36 eV. The fabrication of novel films from renewable recycled PGP platform and advanced carboxylic functionalized CNTs properties will be the key features for many of next forthcoming technologies. The PGP considered as environment‐friendly and easily degradable platforms will be a successful alternative for conventional nondegradable electronic platforms, and water‐dispersed carboxylic functionalized CNTs with advanced properties will be finding accelerating executive applications.